2022
DOI: 10.1177/09612033221107538
|View full text |Cite
|
Sign up to set email alerts
|

Improved pregnancy outcomes in systemic lupus erythematosus: A retrospective study of pregnancies from a single centre in Denmark from 2010–2020 compared with the period 1990–2010

Abstract: Objectives Over the past decades new international guidelines recommend that pregnant Systemic lupus erythematosus (SLE) patients are monitored closely in a multi-professional team throughout pregnancy. The importance of low disease activity before pregnancy and continued treatment during pregnancy has been established. However, there is still a high risk of adverse pregnancy outcome (APO). The APO in a Danish SLE cohort was evaluated and compared with the results in a previous study cohort from the same centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…We also observed a higher prevalence of spontaneous abortion (28%) among patients with SLE compared to the previously reported range (5-22%). 21,[27][28][29][30] A prior study, which used nationwide claims databases in Korea, reported a spontaneous abortion prevalence of 22% but utilized more restricted definition (O02O06) compared to definition used in our study (O01O08). 21 Applying the same definition led to a slightly lower estimated prevalence of spontaneous abortion at 26% (Table S8).…”
Section: E P U B a H E A D O F P R I N Tmentioning
confidence: 77%
See 4 more Smart Citations
“…We also observed a higher prevalence of spontaneous abortion (28%) among patients with SLE compared to the previously reported range (5-22%). 21,[27][28][29][30] A prior study, which used nationwide claims databases in Korea, reported a spontaneous abortion prevalence of 22% but utilized more restricted definition (O02O06) compared to definition used in our study (O01O08). 21 Applying the same definition led to a slightly lower estimated prevalence of spontaneous abortion at 26% (Table S8).…”
Section: E P U B a H E A D O F P R I N Tmentioning
confidence: 77%
“…A key strength of our study is large dataset of pregnant women with SLE, which is particularly valuable due to the rarity of this population. In contrast to previously studies with 100-200 SLE pregnancy cases, our study benefits from increased statistical power [ 26 , 27 , 29 , 31 , 32 ]. Our pregnancy algorithm refined previous outcome-specific methods; however, it is important to emphasize that this algorithm is not a validation study using a database linked with electronic medical records or pregnancy registry.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations